Is the Real Interest Rate Stable? - ROSE, ANDREW K. (Journal of Finance, 1988)
ABSTRACT Univariate time‐series models for consumption, nominal interest rates, and prices each appear to have a single unit root before 1979. If nominal interest rates have a unit root but inflation and inflation forecast errors do not, then ex ante real interest rates have a unit root and are therefore nonstationary. This deduction does not depend on the properties of the unobservable ex post observed real return, which combines the ex ante real interest rate and inflation‐forecasting errors. The unit‐root characteristic of real interest rates is puzzling from at least two perspectives: many models imply that the growth rate of consumption and the real interest rate should have similar time‐series characteristics; also, nominal returns for other assets (e.g., stocks and bonds) appear to have different times‐series properties from those of treasury bills.